Observational study for the functional outcome of humerus shaft fractures treated with plating versus nailing - Bal, Gurwinder Singh; Sandhu, Harinder Singh; Chaudhary, Anil Kumar; Sandhu, Amandeep Kaur (International Journal of Research in Medical Sciences, 2022)
Background: Fractures of the humerus diaphysis comprise approximately 3% of all fractures. It’s treatment has mainly been conservative in the past but is not well tolerated by the patient now a days. Also, all humerus shaft fractures are not amenable to conservative methods. Operative interventions like dynamic compression plating and intramedullary nailing are associated with better functional outcome. There has been a lot of debate on which of the above two surgical methods is better for management of humeral shaft fractures to ensure better functional outcome and lesser complication rate. Objective were to compare the results of the plating and nailing in the treatment of humerus shaft with reference to A) functional outcome and B) complications and their management. Methods: All patients with fracture of humeral shaft presenting to the department of orthopaedics, MMIMSR, during the study period and that met our criteria were included in the study. Out of total 30 patients, 15 were randomly selected for intramedullary nailing and 15 for plating. Postoperatively, these patients were followed up for 6 months and relevant data was collected. Time taken for union, post operative complications rate and final functional outcome were then compared in the two groups. Study design was observational study. Results: It was observed that most of the patient that sustained humeral shaft fractures were 18-40 years of age. Post-operatively, fractures treated by plating united earlier, had lesser complications and significantly better functional outcome compared to nailing. Conclusions: We concluded that plating is a better method and more acceptable to patients as compare to intramedullary nailing for the treatment of fractures shaft humerus, as it is associated with better functional outcome, earlier union of fracture and lesser complication rate.